2022
DOI: 10.1093/ehjci/jeab294
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance-derived left ventricular intraventricular pressure gradients among patients with precapillary pulmonary hypertension

Abstract: Aims Precapillary pulmonary hypertension (pPH) affects left ventricular (LV) function by ventricular interdependence. Since LV ejection fraction (EF) is commonly preserved, LV dysfunction should be assessed with more sensitive techniques. Left atrial (LA) strain and estimation of LV intraventricular pressure gradients (IVPG) may be valuable in detecting subtle changes in LV mechanics; however, the value of these techniques in pPH is unknown. Therefore, the aim of our study is to evaluate LA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…In addition, inter- and intra-observer variability is very limited. 13 In our study, LV-IVPG analysis revealed different patterns in DCM patients, and several parameters were predictive of adverse outcome, independent of known clinical and imaging predictors such as LGE, LA strain, and LV-GLS which have been extensively investigated as important prognostic markers in DCM as well. 26–28 Therefore, this analysis could potentially improve risk stratification and clinical management.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In addition, inter- and intra-observer variability is very limited. 13 In our study, LV-IVPG analysis revealed different patterns in DCM patients, and several parameters were predictive of adverse outcome, independent of known clinical and imaging predictors such as LGE, LA strain, and LV-GLS which have been extensively investigated as important prognostic markers in DCM as well. 26–28 Therefore, this analysis could potentially improve risk stratification and clinical management.…”
Section: Discussionmentioning
confidence: 51%
“… 9 , 22 The association of higher RVEDVi with the IVPG reversal pattern might be explained by ventricular interdependence as is seen in a previous pulmonary hypertension study of ours. 13 Ventricular conduction delay (QRS > 120 ms), indicating dyssynchrony, was associated with an IVPG shift as well. Dyssynchrony is known to influence LV-IVPGs, as is described in a HF study in which the presence of a LBBB altered LV-IVPGs to a more orthogonal direction in early diastole.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have shown that HDF represents a sensible indicator of ventricular function that may show early alterations of ventricular function ( 11 ). HDF analysis can differentiate heart failure patients with preserved ejection fraction compared to controls with similar ejection fraction ( 11 ), reveal subclinical dysfunction due to cardiotoxicity from anthracycline chemotherapy ( 30 ), and it was the first left ventricular parameter to testify the impact of precapillary pulmonary hypertension on cardiac function ( 31 ). As HDF drives the intraventricular pressure gradient exchanged within the myocardium, stimulation of mechanoreceptors may provoke activation of intracellular pathways involved in cardiac adaptation and remodeling ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the study by Vos et al [21] used the same approach as our study in patients with pulmonary hypertension; however, they looked into different parameters, according to the different cardiac phases (systolic ejection, systo-diastolic transition, and the passive and active lling), while we considered HDF throughout the entire cardiac cycle.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%